Pengaruh Akun Instagram Tasya Farasya Terhadap Impulsive Buying Konsumen Kota Bontang - Alinda Diah Syafika; Hairunissa Hairunissa (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aimed to identity the effect of Tasya Farasya's Instagram account on Impulsive Buying in Bontang City. This study case AIDA theory. The sampling technique used is Non Probability Sampling with the sampling method used is Purposive Sampling, where the sampling uses certain criteria. Based on the slovin formula, the researcher distributed questionnaires with a g-form to 100 respondents who were women in the city of Bontang aged 18-40 years. The analysis used was simple linear regression analysis using SPSS version 25. The results showed that the influence of Tasya Farasya accounts had a positive and significant effect on impulsive buying. .